1990
DOI: 10.1007/bf01344309
|View full text |Cite
|
Sign up to set email alerts
|

Movements of blue sharks (Prionace glauca) in depth and course

Abstract: Abstract. Acoustic telemetry was used to follow 22 blue sharks, Prionace glauca (Linnaeus), over the continental shelf and slope in the region between George's Bank and Cape Hatteras between 1979 and 1986. The sharks frequently made vertical excursions between the surface and depths of several hundred meters. The oscillations, which were repeated every few hours, were largest in the daytime and were smaller in amplitude and confined to depths near the thermocline at night. This behavior was prominent in trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
279
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(315 citation statements)
references
References 18 publications
22
279
1
13
Order By: Relevance
“…There also may have been some inhibition of vertical movement for a short time following the initial stress-related dive, but it is unclear whether this was due to tagging stress. Carey & Scharold (1990), Block et al (1997) and(1992) observed similar behavior in blue sharks, yellowfin tuna and blue marlin, respectively, wherein diving patterns were less welldeveloped over approximately the first 12 h of tracking. Although it is difficult to determine the degree to which capture stress impacts post-release behavior, the occurrence of diel vertical movement patterns may provide some indication of speed of recovery that may only be obvious over longer tracks.…”
Section: Vertical Movementsmentioning
confidence: 74%
See 3 more Smart Citations
“…There also may have been some inhibition of vertical movement for a short time following the initial stress-related dive, but it is unclear whether this was due to tagging stress. Carey & Scharold (1990), Block et al (1997) and(1992) observed similar behavior in blue sharks, yellowfin tuna and blue marlin, respectively, wherein diving patterns were less welldeveloped over approximately the first 12 h of tracking. Although it is difficult to determine the degree to which capture stress impacts post-release behavior, the occurrence of diel vertical movement patterns may provide some indication of speed of recovery that may only be obvious over longer tracks.…”
Section: Vertical Movementsmentioning
confidence: 74%
“…This reaction was brief (< 3 h) in most cases, and is well documented as a short-term stress response in various acoustically tagged pelagic fishes (e.g. Sciarrotta & Nelson 1977, Carey & Scharold 1990, Holland et al 1990a, Block et al 1992, Holts & Bedford 1993. There also may have been some inhibition of vertical movement for a short time following the initial stress-related dive, but it is unclear whether this was due to tagging stress.…”
Section: Vertical Movementsmentioning
confidence: 92%
See 2 more Smart Citations
“…These results highlight the importance of accurately delineating movements of individuals at scales relevant to species conservation. Advances in electronic tagging equipment provide a range of tracking technologies that enable assessment of the movement and habitat use of marine species ranging from hours (Carey et al 1990) to years (Block et al 2001) and across individual estuaries (Kneebone et al 2012) to ocean basins (Skomal et al 2009). …”
Section: Introductionmentioning
confidence: 99%